KENDALA DAN PROSPER DEMOKRATISASI DESA PADA ERA OTONOMI DAERAH - M. Syahbudin Latief (Populasi, 2003)
Village democratization has emerged in Indonesia in line with the implementation of regional autonomy policy. In fact, village democratization facing some constraints. One of the serious problems is the blank of political education or civic education as an impact of floating mass policy in rural area, during the New Order era. Besides that, the state apparatus seem not too serious to encourage village democratization, from the beginning the policy has been declared. The socialization process in rural area is very weak. At the implementation stages, formulation of the regional regulation are very rigid. It seems that the state apparatus feel more comprehend about the custom and interest of village people, than the villagers themselves. In this case, the state apparatus seems too arrogant. Basically, the prospect of village democratization is in the village people hand. The support and encouragement from the pro-democratic society, id est intellectuals, academicians, researchers, journalists, NGOs activist, mass organizations, executive and legislative can however, accelerate the practice of village democratization.